changevin term of cotA: secA
Answers
Answered by
1
Answer :
Now, secA
= √(sec²A)
= √(1 + tan²A), since sec²A - tan²A = 1
= √(1 + 1/cot²A), since tanA = 1/cotA
This is the required form.
#MarkAsBrainliest
Now, secA
= √(sec²A)
= √(1 + tan²A), since sec²A - tan²A = 1
= √(1 + 1/cot²A), since tanA = 1/cotA
This is the required form.
#MarkAsBrainliest
Similar questions
India Languages,
8 months ago
English,
8 months ago
Computer Science,
8 months ago
Math,
1 year ago
Physics,
1 year ago
Biology,
1 year ago
Biology,
1 year ago